2018
DOI: 10.5507/bp.2018.035
|View full text |Cite
|
Sign up to set email alerts
|

Retinal abnormatilites as a diagnostic or prognostic marker of schizophrenia

Abstract: The review is a summary of structural and functional changes in the human retina observed in patients with schizophrenia. The main focus is on the potential of these changes to serve as schizophrenia-specific biomarkers accessible to clinicians. We identified three features of the retina that can be detected non-invasively in humans and which appear to show charateristic changes in schizophrenia: (1) retinal microvasculature displaying abnormally wide venules; (2) electroretinograms indicating altered function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…There has been some evidence that vascular inflammatory processes play some roles in schizophrenia pathogenesis, and this forms the basis of our attention to optic nerve vascular densities. 23 We demonstrated that the cup/disc area ratio, and vertical and horizontal cup/disc ratio are significantly higher in patients with schizophrenia than healthy individuals. No statistically significant difference in peripapillary RNFL thickness and vascular parameters in the optic nerve head was observed between the two groups.…”
Section: Discussionmentioning
confidence: 69%
“…There has been some evidence that vascular inflammatory processes play some roles in schizophrenia pathogenesis, and this forms the basis of our attention to optic nerve vascular densities. 23 We demonstrated that the cup/disc area ratio, and vertical and horizontal cup/disc ratio are significantly higher in patients with schizophrenia than healthy individuals. No statistically significant difference in peripapillary RNFL thickness and vascular parameters in the optic nerve head was observed between the two groups.…”
Section: Discussionmentioning
confidence: 69%
“…Ladislav Hosák, MD, PhD, 1 Tomáš Zeman, MSc, PhD, 2,3 Jan Studnička, MD, PhD, 4 Alexandr Stepanov, MD, PhD, 4 Libor Ustohal, MD, PhD, 5 Marek Michalec, MD, PhD, 6 Jan Lochman, MSc, PhD, 2,3 Tomáš Jurečka, MD, PhD, 7 Evgenii Sadykov, MD, PhD, 1 Nandu Goswami, MD, PhD, 8 Patrick De Boever, MSc, PhD, 9,10,11 Vladimir J. Balcar, MSc, PhD, DSc 12 and Omar Šerý, MSc, PhD The treatment of malocclusion with skeletal deformity is managed by both orthognathic surgery and orthodontic treatment. 1 Most orthodontic patients pursue recovery of masticatory function.…”
Section: Disclosure Statementmentioning
confidence: 99%
“…Pending resolution of conflicting evidence 2,3 and inclusion of genetic factors 9 as well as confirmation by larger studies, the measurement of retinal blood vessel diameter could become a screening or diagnostic tool. 10…”
mentioning
confidence: 99%
“…Also, the association between retinal microvasculature and impaired working memory (Appaji et al, 2020) and brain cortical thickness have been reported (Korann et al, 2021). A few authors have also proposed retinal vascular abnormalities as a potential biomarker in schizophrenia (Hosak et al, 2018).…”
Section: Introductionmentioning
confidence: 97%